Awareness education on the prevention and control of upper respiratory tract infections in medical students of Universitas Muhammadiyah Yogyakarta - Widuri, Asti; Daniswara, Deoni; Herdini, Camelia (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Respiratory tract infections are a subject of public health concern due to their widespread occurrence and significant rates of disease and mortality reported worldwide. Viruses trigger most of these respiratory infections, but bacteria also trigger some. Current measures in prevention efforts are to limit the spread of cases. Health education is crucial in preventing and managing infectious diseases. Given the provided background information, the Faculty of Medicine and Health Sciences service team Universitas Muhammadiyah Yogyakarta, conducted awareness education on preventing and controlling upper respiratory tract infections in medical students of Universitas Muhammadiyah Yogyakarta.Methods: The participants of this community service consisted of 49 students. This community service program was carried out in March 2024. The techniques used in implementing this program in detail are preparation before the implementation of community service, pretest, providing educational material on preventing and controlling upper respiratory tract infections and ending with posttest activities. The delivery of educational material was carried out with a PowerPoint presentation for 90 minutes. Results: This community service activity was attended by 49 participants, with the majority of respondents aged 21 years (51%) and females (61.2%). The analysis found a statistically significant increase in knowledge (p=0.000) between before and after education.Conclusion: In this study, education on preventing and managing upper respiratory tract infections proved significant in enhancing knowledge.